SHRINKING CITIES IN POST‐SOCIALIST EUROPE: WHAT CAN WE LEARN FROM THEIR ANALYSIS FOR THEORY BUILDING TODAY?. Issue 4 (December 2016) - Haase, Annegret; Rink, Dieter; Grossmann, Katrin
ABSTRACT: In the final decades of the twentieth century, the post‐industrial regions of western Europe and the US were hot‐spots of urban shrinkage, and this also affected large areas in post‐socialist countries. Despite ongoing calls for a better integration of diverse global urban experiences into theorization, post‐socialist cities and their trajectories, as well as their experiences with rapid urban change, have been largely disregarded in general theory development. At the same time, we face a somewhat inconsistent situation in the theoretical discourse on urban development. There are requests for "new geographies of theory" or to regard all cities as "ordinary", in order to include different types of narratives and experience into overall comparisons and/or theory building. Set against this background, this paper aims to deal with the case of shrinking post‐socialist cities, that is, cities that are "excluded" from hegemonic discourses for two reasons: they are post‐socialist and they are shrinking. In contrast to this situation, we understand shrinking post‐socialist cities as valuable examples for strengthening the debate on current and future forms of, and determining factors for, general urbanization. At the focus of our paper, therefore, are the questions about what we can learn from the analysis of shrinking post‐socialist cities for the general discourse, as well as for theory building for cities, and how we can overcome the observed reluctance to integrate the post‐socialist experience into general theory development. The paper draws on an EU 7 FP research project finished in 2012 that comparatively analysed urban shrinkage across several regions of Europe, with a particular focus on post‐socialist countries.